Using platelet-rich plasma to treat jumper's knees: Exploring the effect of a second closely-timed infiltration. Issue 3 (March 2016) - Kaux, J.F.; Croisier, J.L.; Forthomme, B.; Le Goff, C.; Buhler, F.; Savanier, B.; Delcour, S.; Gothot, A.; Crielaard, J.M.
Abstract: Objectives: Some clinical series have evaluated the effect of platelet-rich plasma (PRP) in the treatment of proximal patellar tendinopathy. Although it is possible that a single infiltrative administration may prove to be an effective treatment for this indication, most of the existing studies evaluated the effects of two or three successive infiltrations. The aim of this study was to evaluate whether two infiltrations of PRP proves more effective than a single treatment. Design: Prospective, randomized and comparative study of level 2. Methods: Twenty patients suffering from chronic proximal patellar tendinopathy were enrolled into the study and split into two randomized groups (one or two infiltrations of PRP, respectively). The 3-month follow-up evaluation consisted of VAS, IKDC and VISA-P scores, along with algometer, isokinetic and ultrasounds evaluations. After 1 year, subjects were contacted to define their functional evolution. Results: The concentration of the PRP used for each infiltration was similar in both groups, and contained no red or white cells. Results revealed no difference in treatment efficacy between the groups. Conclusions: The comparison between one or two infiltrations of PRP did not reveal any difference between the two groups at short to mid term. A second closely-timed infiltration of PRP to treat proximal patellar tendinopathies is not necessary to improve the efficacy of this treatment in the short term.